Biological innovation evaluation in higher education for the reform and exploration of innovation and entrepreneurship course teaching - Zhou, Haijuan; Hou, Yali; Qi, Xiaomeng; Hu, Xuefeng; Liu, Xiangge (Molecular & Cellular Biomechanics, 2025)
Since biological technology is developing so quickly, one of the most important responsibilities for scientific research and technological innovation in higher education institutions is evaluating innovation capability. In order to thoroughly monitor and document the creative advancements made by higher education institutions in the field of biotechnology, this paper suggests a novel assessment technique that blends cutting-edge communication technology with Internet of Things technology. We can create a multifaceted innovation capability evaluation system by using the Internet of Things (IoT) technology to gather a variety of data in real time during biological experiments, including experimental results, feedback information from technology applications, and environmental data of biological samples. This study offers an assessment framework for biological technology innovation that can successfully identify and analyze important technical factors and possible bottleneck issues in the innovation process by combining the real-world scenario of biological research with intelligent computing and machine learning algorithms. According to the experimental data, this approach may reliably assess how well higher education institutions do biological technology research and identify key indications of biological technology innovation. In addition to offering a fresh viewpoint on how to improve the capacity for innovation in biology at higher education institutions, this study offers scientific underpinnings and technical assistance for biotechnology research and implementation.